An Empirical Study For Collaboration of Sir Sayyed Ahmed Khan In the Direction of Muslim Education: The Impact of Sir Sayyed Ahmed Khan's Efforts on Muslim Education and Society during the British Occupation (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Accompanying their pulverizing of the insurgency of 1857,the British merged their mainstream lead in the Indian subcontinent, whichminimized, if not completely disregarded, religion, especially Islam. Theentire of Indiaendured in the backfire, however the outcomes were for the most partobliterating for the Muslims. It was at this basic point that Sayyed Ahmad Khan(1817-1898) courageously approached to counter the risk, and to guard theIslamic trust and Muslim group. He was significantly moved by the desolationthat accompanied the resistance and its regulation. This paper attempts tounderscore the part of the extraordinary reformer in the whatever time wasspent recuperation and restoration of the Muslims. Despite his release by some progressive Muslims as anagnostic, a backstabber and a British operator, Ahmad Khan unequivocallybolstered that Islam is not a religion of brutality however of peace thatregards different religions. He thought about the instructive field, which herightly saw as the best intends to raise the Muslims from their backwardnessand obliviousness versus-the predominant Hindus. Today the greatly regarded Aligarh MuslimUniversity in India is anoticeable landmark of his incredible prescience and extraordinary work forMuslims planet wide. The nineteenth century saw a standout amongst the mostturbulent periods in the history of the Muslim individuals in the Indiansubcontinent, throughout which they lost their political hold there. Throughoutthe war of freedom of 1857, Muslims battled enthusiastically to shake offnonnative administer, however in vain, their sun set in political chaos.1Bahadur Shah Zafar (1837-1857), the final Mughal ruler, lost his throne and wasbanished to Rangoon (Yangon).The Muslims' life, property, and even honour were no longer secure on accountof the British suspicion of their dependability. The British involved Delhi and began a rule ofabhorrence in and around the city. Numerous Muslim villages were attacked,homes set ablaze and the defenseless occupants summarily gunned down. A greatnumber of Muslim houses were looted. On false charges by their neighbours,numerous Muslims were swung from trees without trial. The British response tothe unsuccessful climbing of 1857 proclaimed the orderly pulverization of atime and its exceptionally fundamental structures. The whole milieu and therich Muslim society finished with Mughal rule. Besides this enormous humanmisfortune, the consequent Western social attack terrorized the precise beingof the Ummah and the basics of its religion. After the 1857 rebellion, the Britishunderestimated Islam as a lifestyle. One of the numerous Muslim researchers whostrove against this powerful risk was Sayyed Ahmad Khan who tenably stated,'There was no hardship sent from Heaven, which ere it plunged to earth, did notlook for for its resting spot the homes of Muslims.